Thoracic segmental spinal anaesthesia for laparoscopic cholecystectomy in a case of birt-hogg-dube syndrome - Tushar Kanti Ghosh ,; Roy, Purbasha (Asian Journal of Medical Sciences, 2023)
Birt-Hogg-Dube syndrome is an extremely rare genetic disorder featuring multiple lung cyst or bulla which lead to recurrent spontaneous pneumothorax. Laparoscopic cholecystectomy poses a significant challenge in such cases from anesthetic point of view. Thoracic segmental spinal anesthesia (TSS) is a relatively new and beneficial alternative to general anesthesia to avoid post-operative complications. In this report, we used thoracic segmental spinal successfully in a known case of Birt-Hogg-Dube syndrome to avoid post-operative pneumothorax and discussed the technique and anatomical and physiological consequences. We can conclude that thoracic segmental spinal anesthesia can be used safely and successfully in laparoscopic cholecystectomy specially in cases where general anesthesia is better avoided as in Birt-Hogg-Dube syndrome.